1997
DOI: 10.1046/j.1365-201x.1997.00229.x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of nitric oxide in hepatic arterial blood flow and total hepatic blood volume regulation in pigs

Abstract: The importance of nitric oxide in regulating basal arterial blood flow has been examined in several different vascular beds by intra-arterial infusion of inhibitors of nitric oxide synthesis, but not in the arterial vascular bed of the liver. In the present study, N(G)-nitro-L-arginine (L-NNA), in a dose of 0.5 and 1.0 mumol mL-1 of hepatic arterial blood flow, was infused for 5 min into the hepatic artery in seven pigs anaesthetized with pentobarbital sodium. The haemodynamic effects observed by the first inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 18 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…HABR has been examined in pigs (1,9), dogs (11), sheep (34), and cats (7,14,15,17,19,22). However, because one of the aims of our study was to set up a cirrhosis model in the rat that allows for measurement of hepatic blood flow, we adopted the technique described by Lautt et al (17) with minor modifications.…”
Section: Discussionmentioning
confidence: 99%
“…HABR has been examined in pigs (1,9), dogs (11), sheep (34), and cats (7,14,15,17,19,22). However, because one of the aims of our study was to set up a cirrhosis model in the rat that allows for measurement of hepatic blood flow, we adopted the technique described by Lautt et al (17) with minor modifications.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously found that under anesthesia, local control of hepatic arterial blood flow (Qha) at baseline showed increased gain after NO-synthase (NOS) inhibition, via HABR and autoregulation [6]. Furthermore, Grund et al [9] reported that NO represents an important regulator of Rha but does not mediate the HABR. Since NO normally diminishes autoregulatory control in other organs, inhibition of NOS in the hepatic artery indeed could be expected to increase gain in the HABR.…”
Section: Introductionmentioning
confidence: 96%
“…However, it has also been suggested that endogenous NO does not mediate the HABR under physiological conditions [6,9]. We have previously found that under anesthesia, local control of hepatic arterial blood flow (Qha) at baseline showed increased gain after NO-synthase (NOS) inhibition, via HABR and autoregulation [6].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…2 In the liver, NO has already been shown to modify hepatic vascular resistance at the arterial level and in the microcirculation during arterial pressure variations. [3][4][5][6] However, in these studies, the role of NO was estimated by methodologies using cumulative measurements of derived products of NO metabolism or pharmacological inhibition of NO synthases (NOS). This inhibition itself modifies liver blood flow, precluding any evaluation of NO in autoregulation.…”
mentioning
confidence: 99%